Perbedaan Kadar Pentraxin 3 pada Penderita Hepatitis B Kronis dengan Cirrosis dan Tanpa Cirrosis (Journal of Telenursing (JOTING), 2023)
This study aims to see differences in pentraxin 3 levels in chronic hepatitis B sufferers with cirrosis and without cirrosis. The method uses cross sectional consecutive sampling. The results of this study found a significant difference between the average value of Pentraxin 3 in chronic Hepatitis B patients with liver cirrhosis group compared to the group without liver cirrhosis (p